Trends in household energy-related GHG emissions during COVID-19 in four Chilean cities. Issue 1 (2nd January 2022) - Rojas, Carolina; Simon, François; Muñiz, Iván; Quintana, Marc; Irarrazaval, Felipe; Stamm, Caroline; Santos, Benedita
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has strongly affected economies and human lifestyles globally. The changes observed in domestic energy consumption patterns have had an impact on household greenhouse gas (GHG) emissions. Since GHG emissions inventories are only available at the country level and at annual intervals, most studies have calculated the local emission variations by extrapolating annual emissions with smaller time and territorial scale consumption data. This research presents a bottom-up method, based on the exploitation of a survey addressed to 1200 households, that provides the information to calculate directly the variation in their energy-related GHG emissions, without the need for extrapolations. This method has been applied to four medium-sized Chilean cities with serious air quality problems. Given the high correlation between atmospheric pollutants such as NOx and CO2 emissions, we estimate that before the appearance of COVID-19, per capita CO2 emissions were already high. The results show that space heating-related GHG emissions have increased moderately (between 1 and 6%), while emissions from electricity and gas consumption for non-heating uses have increased significantly (between 8 and 23%). This has harmed the household economy, highlighting the importance of considering socioeconomic aspects when assessing the impact of COVID-19 in its entirety.